Consciously uncertain: A Bayesian analysis of preferences formation - Stimolo, Marco; Beraldo, Sergio; Capasso, Salvatore; Filoso, Valerio (Games, 2022)
We investigate experimentally whether players deliberately use irrelevant market cues to shape their evaluations of a traded item. We implement a repeated Vickrey median price selling auction of an unusual bad where players are informed on the market price and on the three lowest or highest asks. We elicited players' consideration of market signals through a questionnaire at the end of the auction. We find that extreme information has a stronger influence on players' evaluations than the market price. However, players' consideration of the market signals explains their behavioral reactivity to the market price but not to the extremes. Hence, players deliberately use an unbiased estimator of the central tendency of the appraisals distribution, while extreme asks' influence is consistent with a priming effect.